Memperkuat Keharmonisan Keluarga melalui Program Prasekolah Online: Studi Kasus pada Alkindi Online Preschool - Nabila, Hizba; Cahyadi, Teguh Dwi (Jurnal Kajian Gender dan Anak, 2025)
The complexity of family relationships and conditions, which are constantly influenced by various factors, encourages individuals who seek to strengthen family harmony to utilize external support as a tool for realizing and creating a harmonious family. One such example is education, which is an inseparable element of daily human life. Online preschools offer an innovative solution that not only meets the educational needs of children but also opens new opportunities through engaging approaches with the potential to strengthen family harmony. This study aims to explore how the capabilities of Alkindi Online Preschool, as an educational product that upholds values supporting family well-being, can serve as a means to reinforce the harmony of its participants’ families. This research uses a qualitative approach with a case study method. Primary data were obtained from in-depth interviews with current and former student guardians, class teachers, the founder of Alkindi Online Preschool, and a family psychologist, while secondary data were obtained from various literature sources. The results of this study show that Alkindi Online Preschool can be used as an instrument to enhance the family harmony of its participants thanks to the family-oriented values embedded in the concept of “My Mother, My Teacher”, the Qur'an-based curriculum and instillation of Islamic values, the delivery of vision and mission posters, the empowerment of mothers, and the support system for mothers.